1954
DOI: 10.1113/jphysiol.1954.sp005228
|View full text |Cite
|
Sign up to set email alerts
|

Assay of oxytocin in blood

Abstract: The antidiuretic hormone (ADH) of the neurohypophysis can be detected and assayed in blood and urine by numerous methods, and the conditions under which it is released have therefore received much attention (for review see Heller, 1951); the release of oxytocin has been less thoroughly investigated owing to the difficulty of assaying this hormone in body fluids. Methods using the uterus of the rat or guinea-pig in situ have not proved suitable for quantitative work, while assay on the fowl's blood pressure (Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

1957
1957
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Non-specific activity was present principally in those experiments in which glassware was still in use to collect blood, and in these cases the concentration of oxytocin was estimated as the difference in activity before and after treatment with thioglycollate. The validity of this procedure was established by previous work (Bisset and Walker, 1954).…”
Section: Experiments On Water and Chloride Excretionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-specific activity was present principally in those experiments in which glassware was still in use to collect blood, and in these cases the concentration of oxytocin was estimated as the difference in activity before and after treatment with thioglycollate. The validity of this procedure was established by previous work (Bisset and Walker, 1954).…”
Section: Experiments On Water and Chloride Excretionmentioning
confidence: 99%
“…Extraction and assay of oxytocin were carried out by the method of Bisset and Walker (1954). In every instance, except where the total activity was very small, extracts were treated with sodium thioglycollate (Van Dyke, Chow, Greep, and Rothen, 1942), and it was assumed that any activity persisting after this treatment was due not to oxytocin but to some nonspecific factor.…”
Section: Experiments On Water and Chloride Excretionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acid Ethanol Extracts.-Procedures used by Vogt (1953) for the extraction of vasopressin from the hypothalamus and by Bisset and Walker (1954) for the extraction of oxytocic and antidiuretic activity from blood, which are based on the method of Melville (1937), were therefore modified as shown on I u p e r n a t a n t Table I. The interval between decapitation of the animal and immersion of the liver or the kidneys in ice-cold acid ethanol was approximately 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…The neutralization was therefore done in two stages. First, the precipitate formed at pH 4 to 5 was removed by centrifugation and, second, the clear supernatant was then adjusted to pH 7.2 and dialysed as described by Bisset and Walker (1954). Flamephotometric control estimations showed that 30 min.…”
Section: Methodsmentioning
confidence: 99%